Working for you isn't working for me : the ultimate guide to managing your boss - Crowley, Katherine; Elster, Kathi (New York : Portfolio, 2009)
The authors apply their insights to the challenges of working for toxic bosses, outlining a four-step process for self empowerment, handling interpersonal disputes, and detaching oneself from negative behaviors.
Includes index.
Keywords: Managing your boss; Psychology, Industrial